2012
DOI: 10.1002/ar.22483
|View full text |Cite
|
Sign up to set email alerts
|

3D Analysis of the Forearm Rotational Efficiency Variation in Humans

Abstract: Pronosupination is a component of the hominoid orthograde corporal plane that enables primates to execute efficient and sure locomotion in their habitat and is an essential movement for the development of manipulative capacities. We analyze human variability in the rotational efficiency of the pronator teres muscle by applying the biomechanical model created by Galt es et al. (Am J Phys Anthropol 2008; 135:293-300; Am J Phys Anthropol 2009a; 140:589-594) to skeletal remains of a human sample (N ¼ 29) and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…This form of locomotion explains the ape body plane that enabled the acquisition of bipedalism, and many aspects of forelimb anatomy can be explained as adaptations to vertical climbing (Fleagle et al, 1981). Moreover, the orientation of the medial epicondyle in nonhuman primates is related to other functional aspects (Fleagle, 1988;Lague & Jungers, 1996;Seiffert et al, 2000;Ciochon & Gunnell, 2004;MacPhee & Meldrum, 2006), and its form is suggested to be partially determined by the locomotor behaviour of each species (Ibáñez-Gimeno et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This form of locomotion explains the ape body plane that enabled the acquisition of bipedalism, and many aspects of forelimb anatomy can be explained as adaptations to vertical climbing (Fleagle et al, 1981). Moreover, the orientation of the medial epicondyle in nonhuman primates is related to other functional aspects (Fleagle, 1988;Lague & Jungers, 1996;Seiffert et al, 2000;Ciochon & Gunnell, 2004;MacPhee & Meldrum, 2006), and its form is suggested to be partially determined by the locomotor behaviour of each species (Ibáñez-Gimeno et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Only the best preserved extremity of each individual was included in the study, and the sample contained right and left specimens in similar proportions. As medial epicondylar orientation shows no differences between sexes (Ibáñez‐Gimeno et al , ), both male and female individuals were included in the sample. In total, 19 men (10 young and 9 mature adults) and 11 women (eight young and three mature adults) were analysed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations